Flexural Properties of UHPFRC Beams with an Initial Notch - Younes Baghaei Osgouei; Shahriar Tavousi Tafreshi; Masoud Pourbaba (Journal of Rehabilitation in Civil Engineering)
Experimental and numerical studies are carried out in this study to characterize the flexural properties of ultra-high-performance fiber-reinforced concrete (UHPFRC) beams with and without an initial notch reinforced with micro steel fibers in overall ratios of 2% by volume. Dimensions of the notch were 5 mm in width, and 25 mm in height. For this purpose, three-point bending tests were carried out on UHPFRC specimens. Thereafter, numerical studies were carried out to validate experimental findings and in subsequent, sensitivity analyses were carried out to provide better insight with regard to the investigated parameters. Variables of the study were: mesh size, width, height, length, overall size of the beam, tensile strength, compressive strength, modulus of elasticity, crack mouth-opening displacement (CMOD), and crack tip-opening displacement (CTOD). Furthermore, vertical deflection-CMOD findings were compared against available equations in the literature and discussions were made where relevant. Results showed that finer mesh leads to negligible stiffer results with similar observations for the maximum sustained stress by the modulus of elasticity, compressive strength, and width variations. Moreover, 40% increase in the tensile strength led to 47% increase in the sustained stress and doubling the clear span led to 5.5% increase in the sustained stress and 20% peak deflection.; depth variations led to size effect phenomenon and  nonlinear regression analyses successfully captured the flexural load-deflection, load-CMOD, and load-CTOD trends of the flexural beams with coefficient of correlation values ( ) close to unity. Finally, a brief cost analysis was given for the fabrication of 1  of UHPFRC.